Fuzzy Logic in Determining The Control Temperature and Humidity in Plant Factory for Cultivation of Pak choy (Brassica chinensis l.) Hydroponics - Choirul Umam; Sandra Malin Sutan; Yusuf Hendrawan (The Indonesian Green Technology Journal, 2019)
In cultivation of vegetable plants, plant factory system requires flexible approach and resolution methods with a high degree of accuracy, considering the main requirement quality of plant factory is internal environmental conditions that must be a constant value for a long period, while the value of temperature and humidity environment is fluctuate easily. The purpose of this study is to find out the steps of obtaining fuzzy values and knowing the value of PWM (Pulse Width Modulation) output in the plant factory for a set point temperature of 280C and a set point humidity of 75% using the Tsukamoto fuzzy approach. Fuzzy logic is an approach method and problem solving by modeling linear and non-linear functions, the main advantages of this method are being very flexible, high tolerance and high-value precision as well natural language use in this method, so  it can be understood easily. Pak choy plants (Brassica Chinensis L.) can grow ideally at temperatures of 19-30oC and 75% humidity. The steps of research is, first determine the input and output variables which are firm sets. Second,  fuzzy compositions, are the steps of changing input values to the value of  functions involve. Third, inference fuzzy set of Tsukamoto  with the minimum method. Fourth, defuzzication with re-convert data in fuzzy set to crisp data. The last step is to get the output value of the defuzzification result which  converted to PWM (Pulse Width Modulation) value. The calculation results obtained a PWM (Pulse Width Modulation) value of 760.2450 for the set point temperature of 28oC and humidity of 75% in the plant factory of pak choy’s cultivation.Keywords: Fuzzy Logic, Fuzzy Tsukamoto, High Accuracy, Pak Choy, Plant Factory, PWM.